Research Paper: Effect of Custom-Made Insole Fabricated With Medial Heel Skive Technique on Plantar Pressure in Individuals With Patellofemoral Pain Syndrome - Gholam Reza Aminian; Fatemeh Bahramian; Masoumeh Bagherzadeh; Shima Fardipour; Zahra Safaeipour; Ameneh Abedian Avval (University of Social Welfare and Rehabilitation Sciences, 2016)
Objective Knee problems, particularly patellofemoral pain syndrome (PFPS), are one of the common complaints of adolescents and young adults. PFPS is also known as "runner's knee" or "jumper's knee" due to its high prevalence among sportspersons. Its symptoms can be aggravated by ascending and descending stairs, squatting, deep squatting, kneeling, prolonged sitting, standing up from sitting, and running. Hence, it affects many aspects of daily life, including the ability to perform pain-free exercise or work-related activities. Non-surgical treatments such as physiotherapy, insoles, and knee orthoses are commonly used to treat people with PFPS. Insoles with medial heel skive is a new method of insole modification that can control pronation and involves the selective removal of small amounts of medial plantar heel of the positive cast of the foot.  The aim of this study is to evaluate the effects of custom-made insole with medial heel skive technique on plantar pressure in PFPS subjects. Materials & Methods In this controlled before-after study, 14 subjects with PFPS were recruited. Plantar pressure and contact area in eight areas of the foot with and without insole with medial heel skive technique were measured using the Pedar system. A paired t-test was used for statistical analysis.  Results The results of this study showed that the use of insole with medial heel skive technique resulted in decreased plantar pressure in the medial hind foot (P=0.001) compared to without insole. Also, the average plantar pressure (P=0.003) and contact area (P=0.002) in the medial mid-foot with the insole with medial heel skive significantly increased in comparison to without insole. However, no significant change was observed in other regions. Conclusion The above-mentioned insoles managed to control pronation and alter plantar pressure distribution. However, since the insoles simply transferred the pressure from one area to another area and failed to distribute the pressure equitably over the examined regions, they cannot be considered to have improved plantar pressure distribution in patients with PFPS.